The Influence of Institutional Factors on Willingness to Communicate in English as a Second Language (ESL): A Study of Sri Lankan English Medium Students. - Wannakukorala, I.J. (University of Jaffna, 2025)
Effective communication in a second language is essential for language acquisition. Communicative competence in relation to the target language is a crucial factor contributing to success; learners must not only comprehend grammar and vocabulary but also use the language effectively in real-life interaction, adapting to a variety of social and cultural contexts. Though the situation and consequences are diverse, learners’ primary intention in an educational environment is to learn and express them freely without fear of judgement or constraints. Nonetheless, the commonly experienced phenomenon in the English as a Second Language (ESL) context is that many feel authentic nervousness when speaking in front of others in real social contexts, possibly due to fear of making mistakes, lack of confidence in their abilities in the second language, concern how they will be perceived by others or unique institutional cultures and practices. This may demotivate learners, often leading them to choose silence as their preferred language option. In institutional environments, ESL teachers often encounter learners who have high linguistic competence but unwilling to use English for both academic and general communication—they do not feel at ease. This tendency among ESL learners has been a recurrent focus of ESL theorists, who seek to identify the factors influencing Willingness to Communicate (WTC) and how they hinder natural communication which is essential in enhancing Second Language Acquisition (SLA) in learners. The existing literature and research findings indicate that WTC is shaped by both individual and societal factors, ultimately influencing personality-related communicative competence such as self-confidence, anxiety levels, motivation and the willingness to take risks in communication, as well as societal influences like cultural norms, social attitudes toward the use of the target language, and the perceived value of communication in the target language within the community. Yet, the conducted studies on this area are not often found in the existing literature in relation to Sri Lankan ESL context. Even with the efforts of ESL teachers, the availability and the utilization of innovative resources and modern pedagogical approaches mingled with technology, the aforementioned problem remains prevalent in Sri Lankan schools. Therefore, the objective of this study was to investigate this recurrent problem that ESL teachers encounter in the school context; unwillingness to communicate among Sri Lankan learners in their particular institutional cultures that shape the learning environment and influence learners’ attitudes toward communication in English. To carry on the study, a sample of two hundred and forty (240) grade 09 students was deliberately selected from the demography of the Galle education division in the Galle District in the Southern Province of Sri Lanka, with the intention of conducting the research using a mixed-method approach. The study revealed that teaching methodology (28%) and peer influence (24%) had the greatest impact on WTC in English. ESL teacher influence (20%) and school policies (10%) played moderate roles, while teacher-student interaction (8%) and extracurricular opportunities (8%) had the least influence. The findings highlight the need for interactive teacher and peer support to enhance WTC, while the remaining factors were attributed to miscellaneous reasons. The present study helps identify certain context-specific gaps in WTC in English among Sri Lankan and other South-Asian ESL learners. This insight could contribute to developing tailored strategies to enhance communication in English, fostering greater language confidence and proficiency among these learners and helping them overcome barriers to language acquisition, leading to the real-world application of English in the 21st century.
Keywords: Authentic nervousness; Willingness to communicate; Linguistic competence; Affective factors; Socio-cultural context